THE IMPACT OF ESG REPORTING ON THE INFORMATIONAL VALUE OF FINANCIAL STATEMENTS FOR INSTITUTIONAL INVESTORS - Dutchak, Iryna; Derevianko, Svitlana; Vytvytska, Uliana (Social Development: Economic and Legal Issues, 2026)
The study’s relevance stems from the growing role of non-financial disclosure in corporate reporting and the lack of a clear understanding of the extent to which ESG information enhances the quality and suitability of financial data for investment analysis. The article aims to examine the impact of ESG reporting on the information value of financial reporting for decision-making by institutional investors. The research was based on the works of leading domestic and international scientists. The following methods were used in the work: analysis of the scientific literature to study current developments in the subject; generalization and systematization to present the research results. It was found that ESG disclosure significantly expands the analytical potential of financial reporting by including non-financial indicators that reflect long-term risks, sustainable development factors and strategic sustainability of companies. The analyzed modern methodological approaches to assessing ESG factors in financial analytics demonstrated that integrating ESG indicators contributes to a more comprehensive understanding of company performance, though this is accompanied by challenges related to data heterogeneity and methodological inconsistencies. The empirical evidence reviewed confirms the existence of a positive relationship between the level of ESG disclosure and the quality of financial information, particularly in terms of transparency, reduced information asymmetry and increased data reliability. It is found that institutional investors widely use ESG information to improve risk assessment, optimize portfolio allocation and align investment strategies with sustainable development goals, thereby increasing the overall efficiency of capital markets. It is emphasized that, despite the potential of ESG reporting to significantly enhance the information value of financial reporting, its effectiveness depends on the development of uniform standards, improvements in data verification mechanisms, and greater transparency in disclosure practices. Further scientific research is needed to develop integrated models for assessing the combined impact of financial and ESG indicators on investment decision-making, as well as to standardize ESG reporting methodologies.